2008
DOI: 10.1093/brain/awn075
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic localization of the human pedunculopontine nucleus: atlas-based coordinates and validation of a magnetic resonance imaging protocol for direct localization

Abstract: The pedunculopontine nucleus (PPN) is a promising new target for deep brain stimulation (DBS) in parkinsonian patients with gait disturbance and postural instability refractory to other treatment modalities. This region of the brain is unfamiliar territory to most functional neurosurgeons. This paper reviews the anatomy of the human PPN and describes novel, clinically relevant methods for the atlas-based and MRI-based localization of the nucleus. These two methods of PPN localization are evaluated and compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
139
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(148 citation statements)
references
References 25 publications
8
139
1
Order By: Relevance
“…Indeed, the direct involvement of PPN neurons in the control of gait and posture is in line with recent clinical data in PD patients showing that low-frequency electrical stimulation of the PPN area improved axial symptoms (10)(11)(12)(13)(14). The contribution of PPN cholinergic neurons could not have been determined previously from studies that used electrical stimulation or pharmacological manipulations.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Indeed, the direct involvement of PPN neurons in the control of gait and posture is in line with recent clinical data in PD patients showing that low-frequency electrical stimulation of the PPN area improved axial symptoms (10)(11)(12)(13)(14). The contribution of PPN cholinergic neurons could not have been determined previously from studies that used electrical stimulation or pharmacological manipulations.…”
Section: Discussionsupporting
confidence: 66%
“…In PD, among the different nondopaminergic neuronal systems affected (7), cholinergic cell loss was found in the PPN of patients with the most severe dopaminergic degeneration (8). Based on the assumption that gait failure is induced by PPN lesion or dysfunction (9), recent therapeutic trials tested the efficacy of electrical modulation of the PPN in reducing these symptoms in selected parkinsonian patients (10)(11)(12)(13)(14). However, the variability of the results raised doubts about the initial hypothesis and emphasized the need to determine the role of the PPN, in particular its cholinergic part, in gait and posture.…”
Section: Introductionmentioning
confidence: 99%
“…The exact location of the PPN is controversial. Moreover, the PPN is not a closed structure with demarcated boundaries, and is thus elusive to clinically available MRI (Zrinzo et al, 2008). Stereotactic atlases generally rely on cytoarchitectural techniques that identify only the rostral component containing the pars compacta.…”
Section: Where and What Is The Ppn And What Is Its Role In Locomotion?mentioning
confidence: 99%
“…Stereotactic atlases generally rely on cytoarchitectural techniques that identify only the rostral component containing the pars compacta. These atlases have guided many surgical centres to implant only the rostral PPN (Zrinzo et al, 2008;Ferraye et al, 2010). However, it is clear from studies using immunohistochemistry that PPN cholinergic neurons of the pars dissipata [revealed by staining with choline-acetyltransferase antibodies (ChAT5)] extend far more caudally (Mesulam et al, 1989).…”
Section: Where and What Is The Ppn And What Is Its Role In Locomotion?mentioning
confidence: 99%
“…In clinical practice, the location of the PPN on standard clinical imaging can only be inferred from the visualized surrounding structures on MRI (Zrinzo et al, 2008). The PPN lies in the lateral pontine and mesencephalic tegmental reticular zones, straddling the pontomesencephalic junction, with its long axis roughly parallel to that of the fourth ventricle floor.…”
mentioning
confidence: 99%